Relationship and impact of the Analysis and evaluation jobs with employees performance : Survey study - العزاوي غانم ارزوقي; حسين حسين وليد (Journal of Economics and Administrative Sciences, 2012)
The aim the research that definition on the impact a lot of Analysis and evaluation jobs impact in support the employees performance the property that are Analysis and evaluation jobs is one of the jobs however of the human resource management on organization and the impact footpace big on the chractericties and performance of the people and the impact that success of the organization , And here problem stool of the research in the omission the role for the Analysis and evaluation jobs impact in support the employees performance from the upward management in the organization , Polls were adopted as tools for obtaining data and the Department of corporate chalybeate was the field of study . The ready statistical program was used in inputting and processing the studying data , and the major results analysis that is Analysis and evaluation jobs that are impact broad and big on the employees performance , and the research conclusion that Analysis and evaluation jobs that one everything of the play role big on the definition jobs and employees performance, and the research that advise on the necessarily organization attention addition in the jobs Analysis and evaluation and carefully deference on the execution and form that is the help to the support employees performance .